EFFICACY OF MULTIPLE MICRONUTRIENTS SUPPLEMENTATION ON ENERGY INTAKE, CALCIUM AND VITAMIN D LEVELS IN UNDERWEIGHT CHILDREN - Ahmad, Ikhlaq; Fatima, Sadia; Luqman, Muhammad Waqas; Nazli, Rubina; Habib, Syed Hamid; Shah, Inayat (Journal of Ayub Medical College Abbottabad, 2022)
Background: Under-nutrition is a major public health problem worldwide. Several studies have documented the effects of vitamin D and calcium supplements in healthy children and in children with bone abnormalities but the effects of multiple micronutrients supplementation in underweight children is limited in literature. Methods: In this randomized controlled trial 38 participants were recruited and divided into two groups of 19 subjects. On the first day of experimental trial, in fasting state 5cc blood samples were collected from all subjects followed by their anthropometric measurements, and serum levels of calcium and vitamin D. All subjects of one group were given Lipid-based nutritional supplement (LNS) and whereas the other group was given the placebo. After one month of compliance the same measurements were repeated and compared. Results: After one month of supplementation mid-upper arm circumference (p=0.005), weight (p<0.001), height (p=0.000), and BMI-Z score (p=0.002) the energy intake (P<0.001), were significantly increased in LNS as compared to Placebo. However, no improvement was observed in the plasma vitamin D (p=0.44) and calcium levels (p=0.46) of underweight children in both groups. Conclusion: Multi micronutrient supplementations are effective in improving anthropometry in the short duration of time. They also improve the energy intake of underweight children. However, no improvement is observed in levels of vitamin D and calcium in LNS group even after a one-month use.